A Dynamic Channel Selection Algorithm of Data Forwarding in Wireless Mesh Networks. (August 2020) - Yang, Jianjun; Shen, Ju; Guo, Ping
Abstract: Wireless Mesh Networks (WMNs) is an emerging technology in networking, in which the devices (nodes) are configured with multi-radios, making the overall capacity improved significantly. Nodes avoid interference with each other by tuning to different channels of the spectrum space. When a node intends to communicate to other nodes, especially a node far away from it with multiple hops, it is critical to find the channel with largest bandwidth to forward the packet. A dynamic channel selection algorithm is presented in this article, by which each node is able to find its next hop based on the criteria of possible largest channel bandwidth to carry out the forwarding. The novel idea of our approach is that only three past numerical data are kept by each node, and then it is able to calculate the potential bandwidth capacity and continue the most efficient forwarding. Simulations experiments were conducted and the results demonstrated that our mechanism outperforms peer approaches in terms of bandwidth capabilities and delay in Wireless Mesh Networks.